Socialism, Aestheticized Bodies, and International Circuits of Gender: Soviet Female Film Stars in the People’s Republic of China, 1949–1969 - Chen, Tina (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2007)
AbstractThis paper analyses the importance of love relations and sexuality in Soviet film for Chinese socialism in the 1950s and 1960s. By looking at the movement of Soviet women across the Sino-Soviet border — in films and as part of film delegations — I highlight the international circuits of gender that shaped socialist womanhood in China. I examine Chinese discussion of Soviet film stars including Marina Ladynina, Vera Maretskaia, and Marina Kovaleva. I locate the movement away from 'fun-loving post-revolutionary' womanhood associated with Ladynina to socialist womanhood located in struggle and partisanship within the larger context of Maoist theory and Sino-Soviet relations. In my examination of debates over which female film stars were appropriate for China I draw out celebrated and sanctioned couplings of Chinese and Soviet film heroines, such as the links made between Zoya and Zhao Yiman. By looking at how Soviet film stars became part of Chinese political aesthetics, sexuality and love emerge as more important to our understanding of womanhood in Maoist China than has been recognized by most scholars of gender in China. This approach therefore offers a new perspective on Maoist ideologies of gender with its emphasis on non-Chinese bodies as constitutive of gender subjectivities in Maoist China. I argue that while gender in Maoist China was primarily enacted on a national level, internationalism and international circuits of gender were central to its articulation.